SANITARY RISK FACTORS AND MICROBIAL PROFILE IDENTIFICATION BY MALDI-TOF OF STREET READY-TO-EAT MEAT PRODUCTS CONTAMINANTS - Attien, Paul; Dadie, Thomas; SINA, HAZIZ; Kouassi, Clément Kouassi; BABA-MOUSSA, LAMINE (My University, 2017)
Many persons use to eat ready-to-eat meat products sold mostly on the street. The aim of our study was to investigate the microbial contaminants profile of meat products sold on the streets of 5 communes in Abidjan. To reach our goal, a survey was conducted to investigate on the type of customer, meat, the selling points, and the probable causes of food poisoning. Forty samples of each of the three kind of ready-to-eat meat (beef, pork and chicken) were collected in five communes of Abidjan. The microbial quality of the collected meat was determined with conventional methods and confirmed by matrix-assisted laser desorption ionization-time-of-flight mass spectrometry. The results of the survey showed a health risk potentially related to the method of cooking and the type of meat. Out of the 600 samples analyzed, 443 strains were isolated. Among the microorganisms, there are Cocci’s (61.61%) mainly Staphylococcus strains, Bacilli (37.28%) and yeast (1.11%). Staphylococcal strains and Enterobacteriaceae are the most predominant and chicken meat is the most contaminated meat product. Also, some strains (Alloiococcus otitis and Ochrobactrum intermedium) were rarely isolated. The meat products contamination constitutes a health risk which could cause significant income loss for both merchant and consumer.
Keywords: Food Safety; Meat Product; Health Risks Factors; MALDI TOF MS; Abidjan